Analisis Implementasi Capacity Building dalam Penguatan Organisasi Sekolah Tinggi Teologi - Kurniawan, Benoni Dominica; Supriyono, Bambang; Hayat, Ainul (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. Theological Colleges (STT) in Indonesia have an important role in preparing religious leaders and strengthening religious organizations. Facing the challenges, STT needs organizational strengthening based on the development of right management science. This study aimed to analyze the implementation of Merilee Serrill Grindle's capacity building theory in organizational strengthening at STT. Using descriptive qualitative methods, this research was conducted through observation, document study, and in-depth interviews with leaders and staff at STT Satyabhakti (Sati). The result of this research showed that the implementation of capacity building in organizational strengthening at STT Sati is going well, but it is necessary to improve the activities of the incentive system and organizational structure, as well as maximizing the function of leaders in developing organizational goals and objectives.Abstrak. Sekolah Tinggi Teologi (STT) di Indonesia memiliki peran penting dalam mempersiapkan pemuka agama dan memperkuat organisasi keagamaan. Menghadapi tantangan dalam perkembangan zaman STT perlu melakukan penguatan organisasi berdasarkan perkembangan ilmu manajemen yang benar. Penelitian ini bertujuan untuk menganalisis penerapan teori capacity building Merilee Serrill Grindle dalam penguatan organisasi STT. Dengan metode kualitatif deskriptif, penelitian ini dilakukan melalui observasi, studi dokumen, dan wawancara mendalam kepada pimpinan dan staf di STT Satyabhakti (Sati). Hasil penelitian ini menunjukkan bahwa implementasi capacity building dalam penguatan organisasi di STT Sati berjalan dengan baik, namun perlu dilakukan peningkatan pada aktivitas sistem insentif dan struktur organisasi, serta pemaksimalan fungsi pimpinan dalam mengembangkan tujuan dan sasaran organisasi.